2020
DOI: 10.5713/ajas.20.0050
|View full text |Cite
|
Sign up to set email alerts
|

— Invited Review — Amino acid requirements in horses

Abstract: Evaluating amino acid requirements, specifically threonine requirements, in horses will enable better feed formulation and result in economic production, improved animal health, and reduced environmental pollution. However, the current knowledge of protein and amino acid requirements in horses is still limited. Because horses have a unique digestive system and consume a variety of feed ingredients, their protein digestibility may be affected than other species by different feed composition, and thus amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…We identified that 69 signalling pathways were significantly activated ( p < 0.05) with Diana Tools mirPath software (Vlachos et al., 2015 ). The pathways remain diverse, but many of them, such as the TGF‐beta signalling pathway, lysine degradation, ECM‐receptor interactions, adherent junctions and focal adhesions, are involved in the control of normal and OA joints (Kang et al., 2016 ; Mok & Urschel, 2020 ; Shen et al., 2014 ; Van Der Kraan, 2018 ). Other pathways and their roles, including mTOR and HIF‐1 signalling pathways, have been investigated in exercised and sepsis‐related laminitis equine subjects, respectively (Hauss et al., 2021 ; Pawlak et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified that 69 signalling pathways were significantly activated ( p < 0.05) with Diana Tools mirPath software (Vlachos et al., 2015 ). The pathways remain diverse, but many of them, such as the TGF‐beta signalling pathway, lysine degradation, ECM‐receptor interactions, adherent junctions and focal adhesions, are involved in the control of normal and OA joints (Kang et al., 2016 ; Mok & Urschel, 2020 ; Shen et al., 2014 ; Van Der Kraan, 2018 ). Other pathways and their roles, including mTOR and HIF‐1 signalling pathways, have been investigated in exercised and sepsis‐related laminitis equine subjects, respectively (Hauss et al., 2021 ; Pawlak et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both limiting and essential amino acids influence milk production and composition in lactating females ( 37 ). Despite being essential for equines ( 23 ), lysine and threonine's effects on mare milk composition have not been extensively studied. Milk production is a complex process involving biochemical synthesis of nutrients, primarily through the selective uptake and concentration of plasma by mammary epithelial cells ( 16 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The control group received no amino acid supplementation, while the three experimental groups were supplemented with different combinations of lysine and threonine (in powder form) added to their feed bags daily at 09:00 a.m. The supplementation regimen was based on the National Research Council ( 21 ) guidelines for lactating mares weighing 400 kg, adjusted to the mares' actual needs to establish a supplementation gradient ( 22 , 23 ). The specific dosages for each group are detailed in Table 1 , sourced from Xinjiang Sesame Trading Company.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that plasma serine and glycine concentrations rapidly decreased in early pregnant women compared to nonpregnant women (Kalhan et al, 2003). Cysteine is a semi‐essential amino acid that is synthesized from methionine (Mok & Urschel, 2020). These two amino acid metabolic pathways have close linkages (Wang et al, 2013), and the down‐regulated BHMT participated in both pathways, indicating the increase in protein consumption in horse pregnancy.…”
Section: Discussionmentioning
confidence: 99%